Sinergisitas Perencanaan dan Penganggaran Pemerintah Pusat dan Daerah - Herlin Angela Dewi (Perantara Law Review, 2024)
Government has two meanings, namely the function of government or governing activities and government organization or collection of government positions (complex van bestuursorganan). As an organization, government has goals to be achieved, which are no different from organizations in general, especially in terms of activities implemented in order to achieve goals, which are stated in the form of plans. Then government planning can run and succeed if it is supported by adequate budgeting. This study aims to determine the planning and budgeting in local government based on the perspective of state administrative law. Synchronization can lead to duplication of activities within a local government organization. The research method used is normative juridical. The result of study indicates that the connectivity of planning and budgeting in the regions has not been fully implemented in accordance with the applicable laws and regulations and has complied with the general principles of good governance.